Fluoroquinolones Are Useful as Directed Treatment for Complicated UTI in a Setting with a High Prevalence of Quinolone-Resistant Microorganisms - Arturo Artero; Ian López-Cruz; Laura Piles; Juan Alberola; José María Eiros; Sofia Salavert; Manuel Madrazo (MDPI AG, 2023)
Fluoroquinolones (FQs) have been widely used for treating urinary tract infections (UTIs); however, the increasing emergence of resistant strains has compromised their use. We aimed to know the usefulness of FQs for the treatment of community-acquired UTI in a setting with a high prevalence of fluoroquinolone-resistant microorganisms. A prospective observational study of patients diagnosed with community-acquired UTI was conducted, in which their outcomes according to whether they had FQs or not in their empirical and directed treatments were compared. A multivariate analysis was performed to identify risk factors for UTIs due to ciprofloxacin-resistant microorganisms. A total of 419 patients were included; 162 (38.7%) patients were treated with FQs, as empirical treatment in 27 (6.4%), and as directed treatment in 135 (32.2%). In-hospital mortality (2.2% vs. 6.6%, p 0.044) and 30-day mortality (4.4 vs. 11%, p 0.028) were both lower in the group of patients directly treated with FQ, while there were no differences when FQs were used as empirical treatment. A total of 37.2% of the cases were resistant to ciprofloxacin, which was associated with healthcare-associated UTI (OR 2.7, 95% CI 2-3.7) and prior exposure to FQs (OR 2.7, 95 % CI 1.9-3.7). In conclusion, our findings show that in a setting with a high prevalence of community-acquired UTI caused by quinolone-resistant microorganisms, FQs as directed treatment for community-acquired UTI were associated with better outcomes than other antibiotics, but their use as empirical treatment is not indicated, even in those cases without risk factors for quinolones resistance.